Ecstasy induced hepatitis mimicking viral hepatitis. Issue 6 (June 1995) - Dykhuizen, R S; Brunt, P W; Atkinson, P; Simpson, J G; Smith, C C
Abstract : Three cases of jaundice after ingestion of 3, 4-methylenedioxymetamphetamine (MDMA), known as 'ecstasy', are reported and the complications associated with the misuse of this drug, which was initially misrepresented as 'safer than alcohol' are described. Ingestion of 'ecstasy' should be considered when investigating unexplained jaundice in younger patients.